Case report: A rare case of sintilimab-induced gastric stenosis and literature review - Song, Kunkun; Dong, Haoxu; Jiang, Shujun; Xu, Xiaohu; Zhang, Chao; Chen, Qian; Wang, Qi (Frontiers in Oncology, 2023)
Sintilimab is a fully human IgG4 monoclonal antibody against programmed death-1 (PD-1) used to treat classical Hodgkin's lymphoma and various solid tumors. With increasing use of sintilimab, some rare adverse reactions have been reported. Here, we report a case of a 50-year-old woman with squamous non-small cell lung cancer (NSCLC) (metastasis to pericardium and pleura) who received two cycles of 200 mg sintilimab immunotherapy combined with albumin-bound paclitaxel and carboplatin chemotherapy and one cycle of sintilimab monotherapy. She was diagnosed with Sjogren's syndrome (with symptoms of fever, dry mouth, dysphagia, and eating difficulty) after three cycles’ treatment and received standard steroidal therapy. Prior to admission, the patient experienced severe stomach discomfort with vomiting and was hospitalized. Upper gastrointestinal iodine angiography showed significant gastric stenosis as well as lower esophageal stenosis. Subsequent ultrafine gastroscopy revealed ulceration at the stenotic site and an absence of normal peristalsis of the gastric wall. Pathological examination of the lesions showed reactive changes, including ulceration, fibrosis, and inflammatory cell infiltration. After multidisciplinary consultation, it was considered that the patient's gastric stenosis with inflammatory fibrosis changes was due to a sintilimab-induced immune hyperinflammatory reaction. The patient had been treated with standard steroidal therapy since suffering from Sjogren’s syndrome, but the gastric stenotic changes were not relieved. The patient then received regular bouginage of esophago-cardiac stenosis under gastroscopy to physically reexpand the fibrous hyperplasia and stenotic site, enabling normal eating function. To our knowledge, this is the first case of gastric stenosis in a patient with squamous NSCLC after using sintilimab and may help clinicians better understand potential immune-related adverse events due to sintilimab and improve assessment and management.